Second-Line Therapy Tyrosine Kinase Inhibitor for Chronic Phase Chronic Myeloid Leukemia Resistant to Imatinib - Pratiwi, Chici; Rajabto, Wulyo (UI Scholars Hub, 2022)
Since the era of tyrosine kinase inhibitor (TKI) therapy, there has been an increase in the median survival of chronic myeloid leukemia. Nevertheless, nowadays there were several cases of chronic myeloid leukemia that are resistant to the first-line TKIs, so that several second-line TKIs were introduced. Assessment of the therapeutic response was performed using a complete peripheral blood examination, bone marrow aspiration cytogenetic examination, and quantitative BCR-ABL examination. The treatment failure criteria were applied based on the ELN criteria. In selecting the second line TKI should be based on the results of mutation analysis and consider the safety profile of the second line therapy. This paper will discuss the recommendations for second-line therapy TKI, adjusted to the resources in Indonesia.